REKONSEPTUALISASI HUKUM PENGATURAN KEGIATAN EKONOMI NASIONAL DALAM MEWUJUDKAN KEADILAN DISTRIBUSI: KAJIAN PUSTAKA ATAS PRINSIP PEMBAGIAN HASIL EKONOMI YANG BERKEADILAN DALAM PERSPEKTIF KONSTITUSIONAL DAN EKONOMI PANCASILA - Gunawan Widjaja (CV. ADIBA AISHA AMIRA, 2026)
This study aims to reconceptualise the law governing Indonesia's national economic activities in order to realise distributive justice through an in-depth literature review of the principle of equitable distribution of economic benefits from two main perspectives, namely constitutionally based on Articles 33 and 34 of the 1945 Constitution and ideologically through the Pancasila Economic framework, whereby a legal-normative analysis reveals that the current liberal economic paradigm has failed to implement the constitutional mandate regarding state control over strategic production sectors and natural resources for the prosperity of the people, thus requiring legal reforms that integrate the principles of equitable efficiency, mutual cooperation, and humanity. The results of the study show that the constitutional perspective affirms the state's obligation to distribute economic results through redistributive instruments such as progressive natural resource royalties, state-owned enterprise social dividends, and people's empowerment programmes, while Pancasila Economics enriches this reconceptualisation with a family-based mixed economy model that rejects the capitalism-socialism dichotomy, resulting in a new legal paradigm that makes proportional distribution of income a benchmark for the success of national economic regulation amid the challenges of globalisation and energy transition.